2019
DOI: 10.1016/j.pnpbp.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of brain-derived neurotrophic factor in Parkinson's disease: a meta-analysis

Abstract: Brain-derived neurotrophic factor (BDNF), a critical modulator in the neurodevelopment and maintenance of both central and peripheral nervous systems, is regarded as a potential therapeutic target of Parkinson's disease (PD). However, its association with PD remains unclear and the data are inconsistent. To explore the correlation, studies reporting BDNF levels in PD patients and healthy controls are searched and a sample of 1496 participants are pooled in the meta-analysis, demonstrating significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 48 publications
0
39
1
Order By: Relevance
“…Other studies have shown that BDNF levels in plasma are different between females and males (Lommatzsch et al, 2005); however, we did not find significant sex differences in plasma BDNF in our cohort, regardless of disease status. We did detect significant positive correlations between both plasma and salivary BDNF and age, which is in contrast to previous studies in the literature that have found either no effect (Jiang et al, 2019) or modest decreased levels of BDNF with age in blood (Lommatzsch et al, 2005;Ziegenhorn et al, 2007). Importantly, however, we did not find that age was a significant covariate in analyzing the differences in BDNF levels between HD patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have shown that BDNF levels in plasma are different between females and males (Lommatzsch et al, 2005); however, we did not find significant sex differences in plasma BDNF in our cohort, regardless of disease status. We did detect significant positive correlations between both plasma and salivary BDNF and age, which is in contrast to previous studies in the literature that have found either no effect (Jiang et al, 2019) or modest decreased levels of BDNF with age in blood (Lommatzsch et al, 2005;Ziegenhorn et al, 2007). Importantly, however, we did not find that age was a significant covariate in analyzing the differences in BDNF levels between HD patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…BDNF is presumed to be responsible for the survival and repair of neurons, and low plasma BDNF has been thought to be related to neurodegenerative diseases. However, plasma BDNF was found to be elevated, reduced, or identical in patients with PD compared with controls, as demonstrated by a recent meta-analysis conducted by Jiang et al [10]. This inconsistency was also noted by research on the association between BDNF and AD [27].…”
Section: Discussionmentioning
confidence: 91%
“…Blood BDNF has also been investigated for its possible role as a biomarker for PD. Blood BDNF was assumed to be lower in patients with PD than in controls because of the nature of neurodegenerative diseases; however, prior research found heterogenicity to be remarkable [10]. Moreover, the blood BDNF level is dynamic and is affected by numerous environmental factors [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, a large-scale study in which over 600 individuals were participated concluded that significant decrease of serum BDNF levels were observed in patients with AD, frontotemporal dementia, Lewy body dementia, vascular dementia whereas significant increase was confirmed in PD patients [ 139 ]. On the other hand, the latest study of the meta-analysis indeed supports an association between decreased blood concentration of BDNF and PD [ 140 ].…”
Section: Parkinson’s Disease and Bdnfmentioning
confidence: 96%